The Effect of Influencer Credibility and Influencer Attractiveness on Trust and Purchase Intention: A Survey of Instagram Followers of @facetologyofficial in Indonesia - Kayla Putri Ramadhiana; Agung Nugroho Luthfi Imam Fahrudi (International Journal of Economics, Business and Innovation Research, 2025)
With the growing dominance of social media, influencer marketing has become a crucial strategy in shaping consumer trust and purchase intentions. Facetology, a skincare brand active on Instagram, collaborates with mega-influencers to engage its audience. This study investigates the impact of influencer characteristics (i.e., expertise, authenticity, physical attractiveness, and homophily) on customer trust and the subsequent effect of that trust on purchase intention. Grounded in the Stimulus-Organism-Response (SOR) theory, influencer characteristics are viewed as stimuli, trust as the organism, and purchase intention as the response. A total of 174 Instagram followers of @facetologyofficial in Indonesia were surveyed using a purposive sampling method. Data were analyzed using SmartPLS 4. The findings show that all four influencer characteristics have significant effects on trust, which in turn influences purchase intention. These findings highlight the importance of credible and attractive influencers in building customer trust and shaping purchase intentions, especially within the Indonesian cosmetics industry.